Implementasi kedisiplinan Santri dalam Meningkatkan Karakter Positif di pesantren Miftahussholawat Serang Banten - Nenti Nenti; Siti Fatonah; Selnistia Hidayani (CV. Lentera Literasi Indonesia, 2026)
This study aims to analyze the implementation of student discipline in developing positive character at Miftahussholawat Islamic Boarding School, Serang, Banten. The focus of the study is directed at the form of discipline applied, the development process, and its impact on student behavior. This study used a descriptive qualitative method with observation techniques, semi-structured interviews, and documentation to obtain in-depth data. The results of the study indicate that student discipline is formed through habituation of daily routines, direct supervision of administrators, and consistent role models. Habituation of activities such as reciting the Quran, congregational prayer, and cleaning duty has been proven to strengthen the order and responsibility of students. Supervision in the form of reminders and social control helps maintain compliance, especially for students who have lecture activities. The findings also show challenges such as differences in levels of awareness and academic busyness, but the strategy of habituation and role models remains effective in instilling the value of discipline. This study provides novelty through the understanding that the implementation of discipline in Islamic boarding schools is not just a rule, but a process of character education that occurs naturally through daily experiences. The implications of this research confirm that a boarding school system based on habituation and supervision can be an effective model for developing disciplined character in Islamic educational institutions.